2015
DOI: 10.5103/kjsb.2015.25.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Coordination of the Trunk Tilting Angle and Bilateral Lower Limbs According to the Stirrups Length during Trot in Equestrian: Asymmetric Index Development of Overall Movement Index Algorithm

Abstract: Purpose : The purpose of this study was to analyze the coordination of the trunk tilting angle and bilateral lower limbs according to the stirrups length during trot in equestrian.Methods : Participants selected as subject were consisted of adult male(n=7, mean age: 45.00±3.78 yrs, mean height: 172.50±2.44 cm, mean body mass: 76.95±4.40 kg, mean, mean leg length: 97.30±2.60 cm). They were divided into 3-types of stirrups lengths(67 cm, 72 cm, 77 cm) during trot. The variables analyzed were consisted of the tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Throughout their equestrian career, riders are taught that the correct leg position aligns the heel vertically below the hip, with the angulations of the intervening joints compressing or extending to accommodate different stirrup lengths (Hyun and Ryew, 2015). With practise and through the development of muscle memory this becomes a reproducible posture that serves as a reference position that the rider returns to after being perturbed by the movements of the horse.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Throughout their equestrian career, riders are taught that the correct leg position aligns the heel vertically below the hip, with the angulations of the intervening joints compressing or extending to accommodate different stirrup lengths (Hyun and Ryew, 2015). With practise and through the development of muscle memory this becomes a reproducible posture that serves as a reference position that the rider returns to after being perturbed by the movements of the horse.…”
Section: Discussionmentioning
confidence: 99%
“…Although the authors did not further investigate the cause or effects, an illustration in the paper shows a lower position of the right foot in a subject with greater external rotation of the right hip. Another study found that the hip and ankle joints were more extended in the right leg than the left leg when riding at a longer stirrup length (Hyun and Ryew, 2015). The possibility of a relationship between the positional asymmetries and the rider's handedness pattern has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the above, preceded studies reported the interaction effect among horse-saddle-rider ( Greve and Dyson, 2013 ; Harman, 1999 ), position-transition analysis of rider during walk-trot-gallop ( Lovett et al, 2005 ) and interaction between horse and rider ( Münz et al, 2014 ). In recent studies, Hyun and Ryew (2015a , 2015b) reported that keeping stirrup length of 74.04% to lower limb length was more effective in stabilization and posture correction of rider. But there was no study about stride mechanism of horse according to on- or off-riding during walk and trot when reviewed the above studies about stability and effectiveness of riding posture related with motor ability of horse.…”
Section: Introductionmentioning
confidence: 99%